Adhisthana adjoining the steps leading to the main temple - Temples of India Project Team (Jio Institute, 2024)
Broken fragments and debris from the original temple assembled on the adhisthana on the southeast side. The adhisthana has a chandrashila (moonstone) on the third step. The moonstone is a hemispherical stone in the shape of the moon placed at the entrance of Hindu temples and is designed to resemble a lotus flower.